Development of The Word Candy Game as a Media to Improve Chinese Vocabulary - Lumintang, Cecep; Pamuji, Dian Yuni; Irawati, Retno Purnama (Universitas Negeri Semarang, 2025)
This research is motivated by the learning media in the Chuji Hanyu Xiezuo Shang class which not yet using learning media in the form of games, this makes an opportunity to develop new innovations to support teaching and learning activities in the form of Word Candy game to improve mastery of chinese vocabulary. The objectives of this research are: 1) Describes the needs of students for Word Candy media in improving vocabulary mastery, 2) Describes the results of the prototype development of Word Candy media in mastering Chinese, 3) Describes the results of expert validation of Word Candy media in mastering vocabulary in learning Chinese. This study uses the Research and Development (R&D) method with five stages, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, and 5) design revision. Based on the needs analysis, it shows that Word Candy media is approved as a learning medium by both lecturers and students. Proven by the results of validation from media experts getting an average value of 88.4 with a score of 4 which is said that this media is very feasible to use, while validation from material experts shows an average value of 88.5 with a score of 4 which is included in the category of very feasible/appropriate to use as a learning medium. After that, the media was improved according to the suggestions given by media experts and material experts.